2020
DOI: 10.1021/acsami.0c01957
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Fabrication of a Liquid NaK Alloy-Based Membrane Electrode for Sodium-Ion Batteries

Abstract: The room-temperature liquid anode is a feasible method for building dendrite-free alkali-metal-based batteries. The Na−K phase diagram shows a eutectic point as low as 260.53 K with a long liquid range below 298 K with the molar fraction of potassium ranging from 30.48 to 84.99%. However, the NaK alloy exhibits a very high surface tension preventing it from wetting the current collector surface. Herein, a novel homogeneous dual solid−liquid composite in which the liquid alloy is fixed by the solid Na 15 Sn 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…60 The reaction between Na or K and Sn powder can only be performed with melted alkali metals, whereas the NaK alloy reacts at room temperature. 61 The reaction of NaK with Sn powder leads to the formation of solid Na 15 Sn 4 phase as a predominant product. Yang et al reported a new membrane-fabricating method to produce NaKbased battery anodes using this reaction (Fig.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 The reaction between Na or K and Sn powder can only be performed with melted alkali metals, whereas the NaK alloy reacts at room temperature. 61 The reaction of NaK with Sn powder leads to the formation of solid Na 15 Sn 4 phase as a predominant product. Yang et al reported a new membrane-fabricating method to produce NaKbased battery anodes using this reaction (Fig.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…In fact, improving wettability and investigating its driving force is important, given the high surface tension of the NaK alloy as a liquid anode for batteries. 61,62 The most comprehensive review on improving NaK wettability and ionic carrier selection mechanism is presented by Li et al 63 Summarising the most recently published advances in NaK-based liquid anodes, the review shows that the NaK alloy wettability can be improved via high-temperature induction, capillary effect, vacuum inltration, and solid interface protection.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…[19,20] As a typical fusible alloy, sodium-potassium alloy (NaK) possesses a low melting point as low as À 12.7 °C, which can be immiscible to most organic solvents and forms a stable nanofluid suspension with a high surface-to-volume ratio by agitation. [21,22] Herein, we demonstrate a liquid metal interfacial engineering strategy for the succinct synthesis of porous carbon at ambient temperature (Figure 1A). The NaK LM microemulsion in toluene formed under high shear stress generated a highly active interface and a nanoengineered microenvironment for facilitating the reactions between the LM and the CCl 4 precursor.…”
Section: Introductionmentioning
confidence: 99%
“…LMs are routinely processed into nanofluids by low‐energy mechanical agitation, which can control the size, shape, and surface functionalization of nanofluids through the selection of the synthesis medium and composition of LMs [19, 20] . As a typical fusible alloy, sodium–potassium alloy (NaK) possesses a low melting point as low as −12.7 °C, which can be immiscible to most organic solvents and forms a stable nanofluid suspension with a high surface‐to‐volume ratio by agitation [21, 22] . Herein, we demonstrate a liquid metal interfacial engineering strategy for the succinct synthesis of porous carbon at ambient temperature (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the application of SIBs has been severely impeded by exploiting appropriate electrode materials that can satisfy the demands of high energy density and long-term cycling stability. [5] So far, various materials, such as alloy compounds, [6][7][8][9] metal oxides/ sulfides/phosphides, [10][11][12] and carbonaceous materials, [13][14][15][16][17] have been extensively investigated as potential anodes for SIBs. Among them, anatase TiO 2 is continuously attracting intensive attention owing to its good structural stability based on intercalation mechanism, high theoretical specific capacity of about 335 mA h g −1 , environmental benignity, and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%